Czym jest prawdziwa wolność? - Gerald O'Collins (Jesuit University Ignatianum in Krakow, 2017)
"What is true freedom for human beings? Where and how do we ﬁ nd it? Does it consist in abandoning the «constraints» of religious and social principles and embracing a radically autonomous existence? Does real freedom ﬂ ourish in loving, trusting relationships with others - above all with God?" These are the issues Gerald O'Collins wants to deal with in this article. As the Author states, "from the seventeenth century through to the start of the twenty-ﬁ rst century, many writers encouraged the idea that God limits human freedom. Typically they understood freedom as choice - a choice between constraints imposed by God and the authentic autonomy of free human beings. This meant seeing God as competing with human beings for the control of their lives. The choice then became either God or freedom." But is this biblical experience of God's presence among people? Analyzing both social and philosophical reasons, underlying the above standpoint, he shows that "true personal individuality comes by existing in and for other persons. We need each other in order to be ourselves. Being a person does not precede interpersonal relationships, as if we were ﬁ rst persons and only then in relationship". Indeed, "real freedom is found in love and in all trusting relationships that image forth the God from whom we came and to whom we will return. The inner life of the Holy Trinity provides the unparalleled pattern and standard of what it is to be loving and what it is to be free"